Selective extraction and modification of cellulose from sugar cane bagasse (Saccharum officinarum) - Liliana Marcela Rincón Fuentes; Lucia Marlen Moreno Bastidas; Oscar Julio Medina Vargas (Universitas Scientiarum)
This paper’s aim was the synthesis of a flocculant useful in the production of panela as an alternative to replace polyacrylamide and improve food safety in Boyacá, a Colombian district. The cellulose was extracted by using a treatment with potassium hydroxide and followed by acid hydrolysis. From the extracted cellulose, cationic dialdehyde cellulose (CDAC) was synthesized and both cellulose and CDAC were characterized using infrared spectroscopy, FTIR, thermogravimetric analysis (TGA), differential thermal analysis (DSC) Scanning Electron Microscopy (SEM) and RAMAN. The cellulose extracted by hydrolysis from sugarcane bagasse with bleaching, gave yield of 50 % and crystallinity index of 77 %. Its modification to aldehyde is 95 % reliable at a temperature of 65 oC and 2 h; with higher temperature and time the performance is affected. The dialdehyde process allows a modification to be carried out and to be more easily attacked at carbons 2 and 3, leaving cationized cellulose for later use as a flocculant in the panela production process as a traditional solution of flocculants and polyacrylamide. Extraction, modification, and tests for the clarification of the panela juice were carried out in triplicate.